36. CLINICAL, LABORATORY CHARACTERISTICS AND TREATMENT OUTCOMES OF MALARIA IN THE FIRST HALF-TERM AT VIETNAM LEVEL 2 FIELD HOSPITAL No. 6 IN BENTIU, SOUTH SUDAN (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the clinical and laboratory characteristics and treatment outcomes of malaria patients treated at the Vietnam Level 2 Field Hospital No. 6 in Bentiu, South Sudan, during the first six months of the mission.Subjects and methods: This retrospective descriptive study was conducted on 30 patients diagnosed and treated for malaria at Vietnam Level 2 Field Hospital No. 6 from September 2024 to March 2025. Data were collected from medical records including clinical manifestations, hematology - biochemistry tests, and treatment outcomes.Results: The mean age of patients was 40.5 ± 7.7 years; 86.7% were male, and 60% were African. Common symptoms included fever (100%), headache (100%), gastrointestinal disturbances (93.3%), and body aches (96.7%). Only 23.3% presented with classic paroxysmal fever. The rapid diagnostic test was positive in 100% of cases, and malaria smear positivity rate was 86.7%. All infections were caused by Plasmodium falciparum. Laboratory abnormalities included thrombocytopenia (mean platelet count: 103.2 ± 57.9 G/L) and mildly elevated liver enzymes. There were no complications or deaths; the recovery rate was 100%, and the average hospital stay was 3.5 ± 1.2 days.Conclusion: Malaria at Vietnam Level 2 Field Hospital No. 6 presented with diverse and non-specific clinical features. Artemisinin-based therapy remained effective and safe.
Keywords: Malaria; Plasmodium falciparum; Vietnam Level 2 Field Hospital; Bentiu; South Sudan.